2017
DOI: 10.1016/j.berh.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic tests in systemic lupus erythematosus

Abstract: Systemic lupus erythematous (SLE) is a chronic autoimmune inflammatory disease characterized by autoantibodies directed against numerous self-nuclear antigens. Due to the heterogeneous nature of lupus, it has been challenging to identify markers that are sensitive and specific enough for its diagnosis and monitoring. However, with the sequencing of the human genome, rapid development of high throughput approaches has allowed for a better understanding of the etiopathogenesis of complex diseases, including SLE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 97 publications
(118 reference statements)
0
20
0
2
Order By: Relevance
“…Conventional serologic ANAs are of limited sensitivity and/or speci city for diagnosis and monitoring in SLE [27]. Here we reported that MLKL mRNA in the PBMCs could differentiate between SLE patients and HC individuals, the AUC was as high as 0.9277 (95% CI 0.878-0.978) with high sensitivity (81.36%) and speci city (93.3%).…”
Section: Discussionmentioning
confidence: 87%
“…Conventional serologic ANAs are of limited sensitivity and/or speci city for diagnosis and monitoring in SLE [27]. Here we reported that MLKL mRNA in the PBMCs could differentiate between SLE patients and HC individuals, the AUC was as high as 0.9277 (95% CI 0.878-0.978) with high sensitivity (81.36%) and speci city (93.3%).…”
Section: Discussionmentioning
confidence: 87%
“…Conventional serologic ANAs are of limited sensitivity and/or specificity for diagnosis and monitoring in SLE [27]. Here we reported that MLKL mRNA in the PBMCs could differentiate between SLE patients and HC individuals, the AUC was as high as 0.9277 (95% CI 0.878-0.978) with high sensitivity (81.36%) and specificity (93.3%).…”
Section: Discussionmentioning
confidence: 88%
“…Secreted antibodies can also be sequenced from other compartments, as shown recently for paired saliva and serum anti-Ro60 precipitins from patients with primary SS [43]. Overall, this first comprehensive proteomic analysis of precipitating anti-dsDNA IgV peptide repertoires in lupus serum offers a fresh approach for characterizing and monitoring anti-dsDNA clonal populations with MS precision and accuracy, and for comparing their molecular signatures with other high-throughput 'omics' technologies [47]. As the high-affinity, somatically mutated anti-dsDNA autoantibodies profiled herein can be considered to reflect germinal centre-dependent responses, a priority will be to investigate IgV peptide signatures as companion diagnostics for biological therapeutics thought to block autoimmune germinal centre reactions, notably via CD40 ligand blockade [44,45].…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, we have recently used MRM/MS with HCDR3 peptides to track serum rheumatoid factor (RF) clonotypes in patients with primary SS and mixed cryoglobulinaemia, and shown that pathogenic RF signatures appear years before clinical presentation [46]. Overall, this first comprehensive proteomic analysis of precipitating anti-dsDNA IgV peptide repertoires in lupus serum offers a fresh approach for characterizing and monitoring anti-dsDNA clonal populations with MS precision and accuracy, and for comparing their molecular signatures with other high-throughput 'omics' technologies [47].…”
Section: Discussionmentioning
confidence: 99%